Hydrogel wound dressing and preparation method thereof
By using a hydrogel layer and support layer composed of a variety of functional materials to form a wound dressing with composite structure, the problems of insufficient antibacterial performance, poor self-healing ability and poor environmental responsiveness of existing dressings are solved, and multiple functions are achieved. Integrated and personalized care effects.
Patent Information
- Application Number
- CN202411694800.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing wound dressings have insufficient antibacterial properties, poor self-healing ability and poor environmental responsiveness, making it difficult to have various functions such as moisturizing, breathable, antibacterial, self-healing and environmental responsiveness at the same time.
Used with polyvinylpyrrolidone, polycaprolactone, sodium carboxymethylcellulose, chitosan, antibacterial agent, antioxidant, growth factor, temperature-sensitive polymer, graphene quantum dot, self-healing polymer, pH-sensitive A hydrogel layer composed of a polylactic acid film and a breathable polyurethane film form a wound dressing with a composite structure.
It realizes the integration of multiple functions, has strong antibacterial, antioxidant, self-healing and environmental response properties, and can adjust its properties according to changes in the wound environment and provide personalized care effects.
Smart Images

Figure CN119455080A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of medical dressings, and in particular to a hydrogel wound dressing and a preparation method thereof. Background Art
[0002] With the continuous advancement of medical technology, the demand for wound care is also increasing. Modern wound care not only needs to provide basic protection functions, but also needs to have multiple functions such as antibacterial, promoting healing, and reducing scars. Especially when dealing with complex wounds (such as diabetic ulcers, burns, surgical incisions, etc.), higher requirements are placed on dressings.
[0003] Common wound dressings on the market include traditional gauze, biological dressings and hydrogel dressings, but the above wound dressings have the following major defects:
[0004] Insufficient antibacterial properties: Most traditional dressings and some hydrogel dressings lack long-lasting antibacterial properties and can easily lead to wound infection.
[0005] Poor self-healing ability: Existing hydrogel dressings cannot quickly restore their integrity after physical damage, affecting their effectiveness and lifespan.
[0006] Poor environmental responsiveness: Existing dressings are unable to adjust their properties according to changes in the wound environment (such as changes in pH), making it difficult to provide personalized care.
[0007] Insufficient comprehensive performance: It is difficult for a single-component dressing to have multiple functions such as moisturizing, breathability, antibacterial, self-healing and environmental response at the same time. A multi-component combination is required to achieve a comprehensive care effect. Summary of the invention
[0008] The embodiments of the present application provide a hydrogel wound dressing and a preparation method thereof, which are used to solve the problem that the existing dressings have poor antibacterial properties.
[0009] In a first aspect, an embodiment of the present application provides a hydrogel wound dressing, comprising: a hydrogel layer, a support layer and a protective layer, wherein the hydrogel layer is prepared from the following raw material components in the following mass ratio: polyvinyl pyrrolidone 10-15%, polycaprolactone 5-8%, sodium carboxymethyl cellulose 2-4%, chitosan 1-3%, antibacterial agent 0.5-1.5%, antioxidant 0.1-0.3%, growth factor 0.01-0.1%, thermosensitive polymer 0.1-0.5%, graphene quantum dots 0.05-0.15%, self-healing polymer 0.5-1.5%, pH sensitive material 0.5-1.5%, nano titanium dioxide 0.1-0.3%, and the balance is deionized water; the support layer is a porous polylactic acid film with a thickness of 0.1-0.3 mm; the protective layer is a breathable polyurethane film with a thickness of 0.2-0.4 mm.
[0010] Furthermore, the particle size of the graphene quantum dots is 1-10 nm.
[0011] Furthermore, the self-healing polymer is a polyurethane-based self-healing polymer or a polyacrylic acid-based self-healing polymer.
[0012] Furthermore, the pH sensitive material is polyacrylic acid or polymethacrylic acid.
[0013] Furthermore, the thickness of the hydrogel layer is 2-4 mm.
[0014] Furthermore, the antibacterial agent is nanosilver or nanozinc.
[0015] Furthermore, the antioxidant is vitamin E, butylated hydroxyanisole or tocopherol acetate.
[0016] Furthermore, the porous polylactic acid film has a pore size of 50-200 microns and a porosity of 50-80%.
[0017] Furthermore, the air permeability of the breathable polyurethane film is 100-300 g / m 2 / 24h, water vapor transmission rate is 1000-2000g / m 2 / 24h.
[0018] In a second aspect, an embodiment of the present application provides a method for preparing a hydrogel wound dressing, comprising:
[0019] Add polyvinyl pyrrolidone, polycaprolactone, sodium carboxymethyl cellulose, chitosan, antibacterial agent, antioxidant, growth factor, thermosensitive polymer, graphene quantum dots, self-healing polymer, pH sensitive material, and nano-titanium dioxide into deionized water in proportion, stir and dissolve to obtain a mixed solution;
[0020] The resulting mixture was placed in an ultrasonic cleaner to remove bubbles for 10-20 minutes;
[0021] Pour the degassed mixed solution into a mold, and place the porous polylactic acid film so that it is completely immersed in the mixed solution;
[0022] The mold containing the mixed solution is placed in a freeze dryer and freeze-dried for 24-48 hours to form a hydrogel layer. The freeze-drying temperature is -20 to -40°C and the pressure is 10-50Pa.
[0023] attaching a breathable polyurethane film to the surface of the hydrogel layer to form a composite structure;
[0024] The composite structure is cut into desired sizes to obtain a hydrogel wound dressing.
[0025] The hydrogel wound dressing provided in the embodiment of the present invention has the following advantages:
[0026] Synergistic effect of nano-titanium dioxide and graphene quantum dots: Nano-titanium dioxide and graphene quantum dots can effectively kill bacteria under photocatalysis, especially under light conditions, nano-titanium dioxide can generate active oxygen species, destroy bacterial cell walls, and thus enhance the antibacterial effect.
[0027] pH-sensitive materials: In an acidic environment, pH-sensitive materials can further release silver ions in the antibacterial agent to enhance the antibacterial effect. This dual mechanism ensures the high antibacterial performance of the dressing in different environments.
[0028] Antioxidants: Adding antioxidants such as vitamin E, butylated hydroxyanisole (BHA) or tocopherol acetate can effectively scavenge free radicals, prevent wound infection and inflammation, and promote wound healing.
[0029] Self-healing polymers: Polyurethane-based self-healing polymers or polyacrylic acid-based self-healing polymers can automatically repair themselves after physical damage, maintaining the integrity and functionality of the dressing and extending its use time.
[0030] These and other aspects of the present application will become more clearly understood in the description of the following embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0032] Figure 1 The present invention provides a flow chart of a method for preparing a hydrogel wound dressing according to an embodiment of the present application. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] According to the first aspect of the present invention, a hydrogel wound dressing is provided, comprising a hydrogel layer, a support layer and a protective layer, wherein the hydrogel layer is prepared from the following raw material components in the following mass ratio: polyvinyl pyrrolidone 12%, polycaprolactone 6%, sodium carboxymethyl cellulose 3%, chitosan 2%, nano silver 1%, vitamin E 0.2%, growth factor 0.05%, thermosensitive polymer 0.3%, graphene quantum dots 0.1%, polyurethane-based self-healing polymer 1%, polyacrylic acid 1%, nano titanium dioxide 0.2%, and the balance is deionized water. The support layer is a porous polylactic acid film with a thickness of 0.2 mm, a pore size of 100 microns, and a porosity of 60%; the protective layer is a breathable polyurethane film with a thickness of 0.3 mm and a permeability of 200 g / m 2 / 24h, water vapor transmission rate is 1500g / m 2 / 24h.
[0035] Preferably, the self-healing polymer is a polyurethane-based self-healing polymer or a polyacrylic acid-based self-healing polymer.
[0036] The pH sensitive material is polyacrylic acid or polymethacrylic acid.
[0037] The thickness of the hydrogel layer is 2-4 mm.
[0038] The antibacterial agent is nano silver, nano zinc or nano copper.
[0039] The antioxidant is vitamin E, butylated hydroxyanisole or tocopherol acetate.
[0040] The pore size of the porous polylactic acid film is 50-200 microns, and the porosity is 50-80%.
[0041] The air permeability of the breathable polyurethane film is 100-300 g / m 2 / 24h, water vapor transmission rate is 1000-2000g / m 2 / 24h.
[0042] The hydrogel wound dressing of the present invention has the following significant beneficial effects:
[0043] Multi-functional integration: Integrates moisturizing, antibacterial, antioxidant, growth factor, thermosensitivity, self-healing and environmental responsiveness to provide comprehensive care effects.
[0044] Self-healing capability: Ability to automatically restore integrity after physical damage and extend service life.
[0045] For example, diabetic foot ulcers are a common complication that causes slow wound healing and easy infection due to poor blood circulation and neuropathy in diabetic patients. Treatment of diabetic foot ulcers usually requires long-term care and regular dressing changes. However, frequent dressing changes not only increase the economic burden on patients, but may also increase the risk of infection. In this case, self-healing ability becomes an important characteristic of hydrogel wound dressings.
[0046] Patients with diabetic foot usually need to use wound dressings for a long time, and frequent changes will lead to high medical costs. Self-healing dressings can automatically repair themselves after minor injuries, extend their service life, and reduce the number of changes, thereby reducing the financial burden on patients.
[0047] Every time you change a dressing, the risk of infection increases. Self-healing dressings can reduce the number of changes and reduce the probability of infection caused by frequent operations.
[0048] Patients with diabetic foot may accidentally scratch or wear the dressing during daily activities, causing the dressing to break. The self-healing ability can quickly repair these small injuries, maintain the integrity and functionality of the dressing, and avoid contamination and infection caused by damage.
[0049] Diabetic foot ulcers are often accompanied by secretions such as pus and blood, which may cause contamination on the surface of the dressing. Self-healing ability can help repair these contaminated areas and restore the cleaning and antibacterial properties of the dressing.
[0050] Self-healing dressings can provide continuous protection and reduce the discomfort caused by dressing changes. Patients can keep the wound closed and moist for a longer period of time, which is conducive to wound healing.
[0051] Long-term use of the same dressing can bring psychological comfort to patients and reduce the psychological burden of frequent dressing changes.
[0052] In the field or in resource-limited settings, self-healing dressings can reduce the need for backup dressings. The self-healing ability can ensure the continued effectiveness of the dressing even when medical resources are unavailable.
[0053] For patients in remote areas, self-healing dressings could reduce the need for frequent medical visits and increase the feasibility of telemedicine services.
[0054] Environmental responsiveness: Able to adjust its properties according to changes in the wound environment to provide personalized care.
[0055] Biocompatibility and safety: All components have good biocompatibility and safety and will not cause immune or allergic reactions.
[0056] Mechanical properties and breathability: The porous polylactic acid film and breathable polyurethane membrane provide good mechanical strength and breathability, protecting the wound from external contamination.
[0057] In summary, the hydrogel wound dressing of the present invention significantly improves the wound healing speed and effect, and solves the problems of insufficient antibacterial performance, poor self-healing ability and poor environmental responsiveness existing in the prior art.
[0058] The conductivity of graphene quantum dots can enhance the response speed of pH-sensitive materials, allowing them to adapt more quickly to changes in the wound environment.
[0059] When the wound environment is acidic, the pH-sensitive material can increase its permeability, exposing more graphene quantum dots to the wound surface and further enhancing the antibacterial properties.
[0060] Self-healing polymers can quickly recover after physical damage, maintaining the integrity of the dressing.
[0061] pH-sensitive materials can adjust their permeability according to changes in the wound environment, allowing the self-healing polymer to work faster where it is needed.
[0062] When the wound environment is acidic, the pH-sensitive material can increase its permeability and release more nanosilver ions from the hydrogel layer.
[0063] The continuous release of nanosilver can maintain a long-term antibacterial effect, prevent bacteria from growing again, and reduce unnecessary drug waste.
[0064] pH-sensitive materials, such as polyacrylic acid or polymethacrylic acid, change their permeability in an acidic environment. When the pH drops, the molecular chains of these materials undergo conformational changes, causing their structures to become looser, thereby increasing permeability.
[0065] In an acidic environment, the permeability of the pH-sensitive material increases, allowing more nanosilver ions to be released from the hydrogel layer. Nanosilver ions have broad-spectrum antibacterial properties and can effectively kill bacteria and prevent the spread of infection.
[0066] Nano zinc or nano copper: Similarly, these antimicrobial agents will be released more in an acidic environment, enhancing the antimicrobial effect.
[0067] Graphene quantum dots: With excellent conductivity and biocompatibility, they can promote nerve regeneration and improve wound healing. In an acidic environment, due to the increased permeability of pH-sensitive materials, more graphene quantum dots can be exposed to the wound surface, further enhancing their conductivity and antibacterial properties.
[0068] Specifically, when an injury occurs, the wound is usually in the early stages, the inflammatory response is mild, the pH value is close to neutral, and pH-sensitive materials (such as polyacrylic acid or polymethacrylic acid) have small porosity and low permeability, and can slowly release anti-inflammatory ingredients such as antibacterial agents and antioxidants.
[0069] Graphene quantum dots are distributed inside the hydrogel, but because the pH value is close to neutral, most of the graphene quantum dots are still encapsulated in the gel and are not exposed to the wound surface in large quantities.
[0070] The slow release of anti-inflammatory ingredients helps to alleviate the initial inflammatory response, reduce irritation to the wound, and maintain the wound in a stable state, thereby creating a good environment for subsequent healing.
[0071] Over time, the wound begins to show an inflammatory response, and the pH value gradually decreases, becoming an acidic environment.
[0072] As time goes by, the wound begins to show an inflammatory response, and the pH value gradually decreases, presenting an acidic environment.
[0073] In an acidic environment, the porosity and permeability of pH-sensitive materials increase, and more antimicrobial agents and antioxidants are released.
[0074] Due to the increased porosity of the pH-sensitive material, more graphene quantum dots can be exposed on the wound surface. These exposed graphene quantum dots have excellent conductivity and biocompatibility, which can promote nerve regeneration and increase the speed of wound healing.
[0075] The exposed graphene quantum dots can communicate with the quantum dots on the upper layer of the gel through microcurrent, causing changes in the permeability of the upper layer of the gel and further releasing more antibacterial substances.
[0076] The rapid release of antibacterial substances can quickly inhibit bacterial growth and reduce inflammatory responses. At the same time, the conductivity of graphene quantum dots can promote nerve regeneration and accelerate wound healing.
[0077] In cases of severe infection, the wound may become purulent and the pH value may drop further, creating a highly acidic environment.
[0078] In a strongly acidic environment, the porosity of pH-sensitive materials increases significantly, the permeability is greatly improved, and almost all antimicrobial agents and antioxidants are released.
[0079] A large number of graphene quantum dots are exposed on the wound surface, forming an efficient conductive network. These graphene quantum dots can not only communicate through microcurrents to enhance the permeability of the gel, but also directly interact with the bacterial cell wall, destroying the bacterial structure and enhancing the antibacterial effect.
[0080] The conductivity and biocompatibility of graphene quantum dots can also regulate the wound microenvironment, promote tissue repair and regeneration, and reduce inflammation and scar formation.
[0081] In purulent wounds, the synergistic effect of pH-sensitive materials and graphene quantum dots can quickly eliminate inflammation, inhibit bacterial growth, promote wound healing, and reduce the risk of infection.
[0082] Self-healing polymers: After physical damage, self-healing polymers can quickly restore their integrity and maintain the performance of the dressing. In acidic environments, due to the increased permeability of pH-sensitive materials, self-healing polymers can respond to physical damage more quickly and restore the integrity of the dressing.
[0083] Thermosensitive polymers: adjust their properties according to temperature changes, such as changing permeability and release rate. In acidic environments, thermosensitive polymers can better adapt to local temperature changes, further optimizing the performance of the dressing.
[0084] Specifically, a thermosensitive polymer is a material that can adjust its physical and chemical properties according to temperature changes. In hydrogel wound dressings, thermosensitive polymers can adjust their permeability and release rate according to changes in local temperature. This property prevents the dressing from releasing its main ingredients when it is not attached to the human body, but after being attached to the human body, it will release its main ingredients at a temperature close to 37°C, thus ensuring long-term stable storage and efficient use of the material.
[0085] When not attached to the human body, the thermosensitive polymer is in a low-temperature environment (such as room temperature 20-25°C), its structure is relatively tight, and its permeability is low. The main ingredients (such as antibacterial agents, antioxidants, growth factors, etc.) are wrapped inside the hydrogel and will not be easily released.
[0086] The low-temperature stability of the thermosensitive polymer ensures that the dressing can remain stable for a long time before use and will not fail due to premature release of ingredients.
[0087] This feature makes the dressing more convenient during transportation and storage, without the need for special refrigeration conditions, thus reducing logistics costs.
[0088] When the dressing is applied to human skin, the local temperature rises to nearly 37°C, the structure of the thermosensitive polymer changes, the permeability increases, and the main ingredients begin to be released slowly.
[0089] In an acidic environment, the porosity and permeability of pH-sensitive materials increase, further promoting the release of the main components.
[0090] As the main ingredients are released, more graphene quantum dots are exposed to the wound surface, enhancing its conductivity and antibacterial properties.
[0091] The structural changes of the thermosensitive polymer enable it to better adapt to local temperature changes, further optimizing the performance of the dressing and ensuring the continuous and controlled release of the ingredients.
[0092] Antimicrobial agents are slowly released at temperatures close to 37°C, which can continuously kill bacteria and prevent infection.
[0093] The release of antioxidants helps scavenge free radicals, reduce inflammation, and promote wound healing.
[0094] The release of growth factors can stimulate cell proliferation and migration, accelerating the wound healing process.
[0095] In inflamed and infected wounds, the local temperature may increase slightly, and thermosensitive polymers can respond more quickly to this temperature change, increasing permeability and accelerating the release of key ingredients.
[0096] The synergistic effect of pH-sensitive materials and graphene quantum dots is further enhanced, releasing more antibacterial substances, rapidly inhibiting bacterial growth and alleviating inflammatory responses.
[0097] Nano-titanium dioxide: It has photocatalytic antibacterial properties and can enhance the antibacterial effect of dressings. In an acidic environment, nano-titanium dioxide works synergistically with graphene quantum dots and pH-sensitive materials to further improve the antibacterial properties.
[0098] Specifically, when an injury occurs, the wound is usually in the early stages, the inflammatory response is mild, and the pH value is close to neutral.
[0099] Under light conditions, nano-titanium dioxide can generate reactive oxygen species (such as superoxide anions, hydrogen peroxide and hydroxyl radicals), which can destroy bacterial cell walls and kill bacteria.
[0100] Graphene quantum dots are distributed inside the hydrogel. Since the pH value is close to neutral, most of the graphene quantum dots are still wrapped in the gel and will not be exposed to the wound surface in large quantities.
[0101] At this point, the pH-sensitive material has a smaller porosity and lower permeability, allowing it to slowly release anti-inflammatory ingredients such as antimicrobial agents and antioxidants.
[0102] The photocatalytic antibacterial properties of nano-titanium dioxide and the slowly released anti-inflammatory ingredients work together to help alleviate the initial inflammatory response, reduce irritation to the wound, and maintain the wound in a stable state, thereby creating a good environment for subsequent healing.
[0103] Over time, the wound begins to show an inflammatory response, and the pH value gradually decreases, becoming an acidic environment.
[0104] In an acidic environment, the photocatalytic activity of nano-titanium dioxide is enhanced, generating more active oxygen species, further improving the antibacterial effect.
[0105] Due to the increased porosity of the pH-sensitive material, more graphene quantum dots can be exposed on the wound surface. These exposed graphene quantum dots have excellent conductivity and biocompatibility, which can promote nerve regeneration and increase the speed of wound healing.
[0106] In an acidic environment, the porosity and permeability of pH-sensitive materials increase, and more antimicrobial agents and antioxidants are released.
[0107] The exposed graphene quantum dots can communicate with the quantum dots on the upper layer of the gel through microcurrent, causing changes in the permeability of the upper layer of the gel and further releasing more antibacterial substances.
[0108] The photocatalytic antibacterial properties of nano-titanium dioxide and the conductivity of graphene quantum dots work together to rapidly inhibit bacterial growth, reduce inflammatory responses, and promote nerve regeneration and wound healing.
[0109] In cases of severe infection, the wound may become purulent and the pH value may drop further, creating a highly acidic environment.
[0110] In a strongly acidic environment, the photocatalytic activity of nano-titanium dioxide reaches its highest level, generating a large number of reactive oxygen species that can quickly kill bacteria and reduce infection.
[0111] A large number of graphene quantum dots are exposed on the wound surface, forming an efficient conductive network. These graphene quantum dots can not only communicate through microcurrents to enhance the permeability of the gel, but also directly interact with the bacterial cell wall, destroying the bacterial structure and enhancing the antibacterial effect.
[0112] In a strongly acidic environment, the porosity of pH-sensitive materials increases significantly, the permeability is greatly improved, and almost all antimicrobial agents and antioxidants are released.
[0113] The conductivity and biocompatibility of graphene quantum dots can also regulate the wound microenvironment, promote tissue repair and regeneration, and reduce inflammation and scar formation.
[0114] In purulent wounds, the synergistic effect of nano-titanium dioxide, graphene quantum dots and pH-sensitive materials can quickly eliminate inflammation, inhibit bacterial growth, promote wound healing and reduce the risk of infection.
[0115] The preparation method of the hydrogel wound dressing is as follows:
[0116] Mixing raw materials: adding polyvinyl pyrrolidone, polycaprolactone, sodium carboxymethyl cellulose, chitosan, antibacterial agent, antioxidant, growth factor, thermosensitive polymer, graphene quantum dots, self-healing polymer, pH sensitive material and nano titanium dioxide into deionized water in proportion, stirring and dissolving to obtain a mixed solution.
[0117] Degassing: Place the resulting mixture in an ultrasonic cleaner to degas for 10-20 minutes.
[0118] Pour into mold: Pour the degassed mixture into the mold and place the porous polylactic acid film so that it is completely immersed in the mixture.
[0119] Freeze drying: Place the mold containing the mixed liquid in a freeze dryer and freeze dry for 24-48 hours to form a hydrogel layer. The freeze drying temperature is -20 to -40°C and the pressure is 10-50Pa.
[0120] Attaching the protective layer: attaching the breathable polyurethane film to the surface of the hydrogel layer to form a composite structure.
[0121] Cutting and packaging: The composite structure is cut into required sizes to obtain a hydrogel wound dressing.
[0122] Example 1
[0123] Hydrogel layer formula:
[0124] Polyvinylpyrrolidone: 12g;
[0125] Polycaprolactone: 6g;
[0126] Sodium carboxymethyl cellulose: 3g;
[0127] Chitosan: 2g;
[0128] Antimicrobial agent (nanosilver): 1g;
[0129] Antioxidant (vitamin E): 0.2g;
[0130] Growth factor: 0.05 g;
[0131] Thermosensitive polymer: 0.3 g;
[0132] Graphene quantum dots (particle size 5nm): 0.1g;
[0133] Self-healing polymer (polyurethane-based): 1g;
[0134] pH sensitive material (polyacrylic acid): 1 g;
[0135] Nano titanium dioxide: 0.2g;
[0136] Deionized water: make up to 100g;
[0137] Support layer:
[0138] Porous polylactic acid film, pore size 100 μm, porosity 60%;
[0139] Protective layer:
[0140] Breathable polyurethane membrane, air permeability 200g / m 2 / 24h, water vapor transmission rate 1500g / m 2 / 24h;
[0141] Example 2
[0142] Same as Example 1, except that the type of antibacterial agent is changed, antibacterial agent: nano zinc 1g.
[0143] Example 3
[0144] The same as Example 1, except that the type of antioxidant is changed, antioxidant: butylated hydroxyanisole (butylated hydroxyanisole) 0.2g.
[0145] Example 4
[0146] The same as Example 1, except that the type of self-healing polymer is changed, self-healing polymer: polyacrylic acid-based self-healing polymer 1g.
[0147] Example 5
[0148] Same as Example 1, except that the particle size of graphene quantum dots is changed, graphene quantum dots (particle size 10 nm): 0.1 g.
[0149] Example 6
[0150] The same as Example 1, except that the type of pH sensitive material is changed, pH sensitive material: 1 g of polymethacrylic acid.
[0151] Comparative Example 1
[0152] Same as Example 1, except that no graphene quantum dots are contained, graphene quantum dots: 0 g.
[0153] Comparative Example 2
[0154] Same as Example 1, except that no pH sensitive material is contained, pH sensitive material: 0 g.
[0155] Comparative Example 3
[0156] Same as Example 1, except that no self-healing polymer is contained, self-healing polymer: 0 g.
[0157] Comparative Example 4
[0158] Same as Example 1, except that no antibacterial agent is contained, antibacterial agent: 0 g.
[0159] Comparative Example 5
[0160] Same as Example 1, except that no antioxidant is contained, antioxidant: 0 g.
[0161] Comparative Example 6
[0162] Same as Example 1, except that no growth factor is contained, growth factor: 0g.
[0163] Experimental example:
[0164] In this experimental example, the hydrogel wound dressings obtained in Examples 1-6 and Comparative Examples 1-6 were tested for antibacterial performance, antioxidant performance, self-healing performance and wound healing performance.
[0165] Antibacterial performance test: Escherichia coli and Staphylococcus aureus were used as test strains, and the bacterial survival rate was determined by the plate count method to evaluate the antibacterial effect.
[0166] Antioxidant performance test: The antioxidant capacity of antioxidants was evaluated through DPPH free radical scavenging experiment.
[0167] Self-healing performance test: The self-healing efficiency of the self-healing polymer was evaluated through cutting-healing experiments.
[0168] Biocompatibility test: MTT assay was performed using L929 cell line to evaluate the cytotoxicity of the materials.
[0169] Wound healing performance test: Through animal experiments, observe the effect of dressings on wound healing speed.
[0170] The specific test results are shown in Table 1.
[0171] Table 1. Performance test of hydrogel wound dressing
[0172]
[0173]
[0174] The antibacterial rates of Example 1 and Example 2 are 98% and 95% respectively, indicating that both nano-silver and nano-zinc have good antibacterial effects, but the effect of nano-silver is slightly better.
[0175] The antibacterial rate of Comparative Example 4 (without antibacterial agent) is 0%, indicating that antibacterial agents are indispensable in hydrogel wound dressings and can significantly improve the antibacterial performance.
[0176] The DPPH scavenging rates of Example 1 and Example 3 were 85% and 90% respectively, indicating that both vitamin E and butylated hydroxyanisole have good antioxidant capacity, but vitamin E has a better effect.
[0177] The DPPH scavenging rate of Comparative Example 5 (without antioxidant) was 70%, indicating that antioxidants can significantly improve the antioxidant properties of the hydrogel.
[0178] The self-healing efficiencies of Example 1 and Example 4 are 90% and 95% respectively, indicating that both the polyurethane-based self-healing polymer and the polyacrylic acid-based self-healing polymer exhibit good self-healing properties, but the polyurethane-based one has a better effect.
[0179] The self-healing efficiency of Comparative Example 3 (without the self-healing polymer) is 70%, indicating that the self-healing polymer can significantly improve the self-healing ability of the hydrogel.
[0180] The antibacterial rates of Example 1 and Example 5 are both 98%, indicating that the change in the particle size of graphene quantum dots has little effect on the antibacterial effect.
[0181] The antibacterial rate of Comparative Example 1 (without graphene quantum dots) is 80%, indicating that graphene quantum dots can significantly improve the antibacterial effect and photocatalytic activity.
[0182] The antibacterial rates of Example 1 and Example 6 are both 98%, indicating that both polyacrylic acid and polymethacrylic acid can release silver ions in an acidic environment to enhance the antibacterial effect, but the effect of polyacrylic acid is more obvious.
[0183] The self-healing efficiency of Comparative Example 2 (without pH-sensitive material) is 80%, indicating that pH-sensitive materials can significantly improve the self-healing performance and antibacterial effect of the hydrogel.
[0184] The wound healing time of Example 1 and Comparative Example 6 (without growth factors) was 7 days and 9 days respectively, indicating that growth factors have a significant effect on promoting wound healing.
[0185] By comparing the above embodiments and comparative examples, the following comprehensive conclusions can be drawn:
[0186] Antimicrobial agents: Both nanosilver and nanozinc can significantly improve the antimicrobial properties of hydrogel wound dressings, with nanosilver having a better effect.
[0187] Antioxidants: Vitamin E and butylated hydroxyanisole can significantly improve the antioxidant properties of hydrogels, among which vitamin E has a better effect.
[0188] Self-healing polymers: Both polyurethane-based self-healing polymers and polyacrylic acid-based self-healing polymers can significantly improve the self-healing ability of hydrogels, among which the polyurethane-based effect is better.
[0189] Graphene quantum dots: Graphene quantum dots can significantly improve the antibacterial effect and photocatalytic activity of hydrogels and are an indispensable component.
[0190] pH-sensitive materials: Both polyacrylic acid and polymethacrylic acid can release silver ions in an acidic environment to enhance the antibacterial effect, among which the effect of polyacrylic acid is more obvious.
[0191] Growth factors: Growth factors can significantly promote wound healing and shorten the healing time.
[0192] In summary, the hydrogel wound dressing provided by the present invention has excellent performance in antibacterial, anti-oxidative, self-healing and promoting wound healing, and has broad application prospects.
[0193] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A hydrogel wound dressing, characterized in that: The invention comprises a hydrogel layer, a supporting layer and a protective layer, wherein the hydrogel layer is prepared from the following raw material components in the following mass ratio: 10-15% polyvinyl pyrrolidone, 5-8% polycaprolactone, 2-4% sodium carboxymethyl cellulose, 1-3% chitosan, 0.5-1.5% antibacterial agent, 0.1-0.3% antioxidant, 0.01-0.1% growth factor, 0.1-0.5% thermosensitive polymer, 0.05-0.15% graphene quantum dots, 0.5-1.5% self-healing polymer, 0.5-1.5% pH sensitive material, 0.1-0.3% nano titanium dioxide, and the balance is deionized water; the supporting layer is a porous polylactic acid film with a thickness of 0.1-0.3mm; the protective layer is a breathable polyurethane film with a thickness of 0.2-0.4mm.
2. The hydrogel wound dressing according to claim 1, characterized in that The particle size of the graphene quantum dots is 1-10 nm.
3. The hydrogel wound dressing according to claim 1, characterized in that The self-healing polymer is a polyurethane-based self-healing polymer or a polyacrylic acid-based self-healing polymer.
4. The hydrogel wound dressing according to claim 1, characterized in that The pH sensitive material is polyacrylic acid or polymethacrylic acid.
5. The hydrogel wound dressing according to claim 1, characterized in that The thickness of the hydrogel layer is 2-4 mm.
6. The hydrogel wound dressing according to claim 1, characterized in that The antibacterial agent is nano silver or nano zinc.
7. The hydrogel wound dressing according to claim 1, characterized in that The antioxidant is vitamin E, butylated hydroxyanisole or tocopherol acetate.
8. The hydrogel wound dressing according to claim 1, characterized in that The pore size of the porous polylactic acid film is 50-200 microns, and the porosity is 50-80%.
9. The hydrogel wound dressing according to claim 1, characterized in that: The air permeability of the breathable polyurethane film is 100-300 g / m 2 / 24h, water vapor transmission rate is 1000-2000g / m 2 / 24h.
10. A method for preparing a hydrogel wound dressing, characterized in that: The following steps are involved: Add polyvinyl pyrrolidone, polycaprolactone, sodium carboxymethyl cellulose, chitosan, antibacterial agent, antioxidant, growth factor, thermosensitive polymer, graphene quantum dots, self-healing polymer, pH sensitive material, and nano-titanium dioxide into deionized water in proportion, stir and dissolve to obtain a mixed solution; The resulting mixture was placed in an ultrasonic cleaner to remove bubbles for 10-20 minutes; Pour the degassed mixed solution into a mold, and place the porous polylactic acid film so that it is completely immersed in the mixed solution; The mold containing the mixed solution is placed in a freeze dryer and freeze-dried for 24-48 hours to form a hydrogel layer. The freeze-drying temperature is -20 to -40°C and the pressure is 10-50Pa. attaching a breathable polyurethane film to the surface of the hydrogel layer to form a composite structure; The composite structure is cut into desired sizes to obtain a hydrogel wound dressing.
Citation Information
Patent Citations
Natural polysaccharide / nano-TiO2 composite light-sensitive antimicrobial hydrogel dressing and radiation synthesis method thereof
CN104043144A
Hydrogel antibacterial gauze dressing and preparation method therefor
CN104906620A
Alkoxyether dendritic chitosan, hydrogel material thereof and preparation method thereof
CN108484797A
Star polymer and self-healing hydrogel with temperature response, pH response and carbon dioxide response and their preparation methods
CN108659241A
Polydopamine particles-doped star-shaped polymer of multi-responsive self-healing hydrogel, and self-healing hydrogel and preparation method thereof
CN108912264A
Cited By
Wound dressing for chronic wound nursing and preparation method thereof
CN121313907A
Glucose / oxidative stress dual-responsive double-layer hydrogel dressing, preparation method and application thereof
CN122624726A